2021
DOI: 10.1016/j.bj.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of multi-epitope peptide-based vaccines against SARS-CoV-2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a pandemic involving so far more than 15 million infections and 630,211 deaths. Effective vaccines are urgently needed to prevent SARS-CoV-2 infections. No vaccines have yet been approved for licensure by regulatory agencies. Even though host immune responses to SARS-CoV-2 infections are beginning to be unravelled, effective clearance of virus will depend on both humoral and cellular immunity. Additionally, the presence of Spike (S)-glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 71 publications
7
32
0
Order By: Relevance
“…These cells uptake LNPs and express the mRNA-encoded antigen which is further processed by the proteasome to generate peptide epitopes which are presented in the cell membrane. Subsequently, APC migrate to nearby draining lymph nodes where T-cell priming occurs [ 12 , 13 ]. Likewise, passive drainage of mRNA–LNPs through lymphatic vessels allows direct delivery of mRNA to the lymph nodes containing resident antigen-presenting cells and T-cells within them [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These cells uptake LNPs and express the mRNA-encoded antigen which is further processed by the proteasome to generate peptide epitopes which are presented in the cell membrane. Subsequently, APC migrate to nearby draining lymph nodes where T-cell priming occurs [ 12 , 13 ]. Likewise, passive drainage of mRNA–LNPs through lymphatic vessels allows direct delivery of mRNA to the lymph nodes containing resident antigen-presenting cells and T-cells within them [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To select specific immunogenic epitopes and accelerate vaccine development, the SARS-CoV-2 genes were analyzed for B and T cell epitope candidates. In addition, the authors propose to increase the low immunogenicity of a peptide vaccine by including an adjuvant in its composition and using an effective delivery system based on chitosan or a copolymer of lactic and glycolic acid (PLGA) [ 291 ]. It is suggested that peptides derived from the short-palate, lung and nasal epithelial clone-1 (SPLUNC1), alpha-1-antitrypsin (AAT), dornase alfa (DA) and neutralizing human S230 light chain antibodies can be used as anti-adhesion agents, preventing the SARS-CoV-2 virus from interacting with the human host cell.…”
Section: Prediction and Development Of New Ampsmentioning
confidence: 99%
“…Many nucleic acid based vaccines encode a whole genome or whole structural motifs. Encapsulating whole S-protein can trigger a broad spectrum of both humoral and cellular immune responses due to large repository of potent epitopes [ 250 ]. Previous vaccine development projects against SARS and MARS group of coronavirus; widely experienced similar prejudices from antibody dependent infection enhancement and that can cause life threatening allergic infection due to establishment of non-neutralizing antibody pool, which gradually increases infection [ 251 ].…”
Section: Cellular Pathways Triggered By Sars-cov-2mentioning
confidence: 99%